THE USAGE OF GADGETS FOR RELIGIOUS ACTIVITIES AMONG MUSLIM TEENAGERS IN YOGYAKARTA - Hapsari, Twediana Budi; Vebrynda, Rhafidilla (International Journal of Psychosocial Rehabilitation, 2020)
The technological change has always affected to the existence of the society, not only as aid to daily activities but also how they interact and doing religious activities. This study describes the gadget utilization among Muslim teenagers for their daily religious activities. The data were gathered from 490 Muslim teenagers across five regencies in Yogyakarta province in 2018. The data analysis was conducted through clustering the respondents’ daily religious activities, religious activities using the gadget, their interest in Islamic issues, and their lifestyles. This study results in four clusters of Muslim teenagers in term of their religious movement using devices related to their lifestyles and interest in Islamic issues. The four groups are religious minimalist, religious activist, intellectual religious and millennial religious.